The motivation of reading of vocational-technical (VT) schoolchildren - Mockienė, Birutė (Knygotyra, 1990)
The investigation of reading motivation is important in studying, regulating, and prognosing the development of personalities. The article deals with the investigation of one thousand vocational-technical schoolchildren and 300 teachers and tutors from seven schools. The data was collected through questionnaires, interviews, and observation. The computer of Vilnius University was used to amend the collected material. The reading motivation of regular and irregular readers was different. Some differences in the motivation of girls and boys were found. The reading motivation of VT schoolchildren is complicated, unstable, and not a strong construct, reflecting the main socio-psychological features of VT schoolchildren’s socialization period. One-third of the tested young people indicated that reading is a matter of great importance. Another part of the schoolchildren expressed their positive but passive standpoint. The main obstacles in reading activity are time deficit, difficulties in finding interesting literature to read, challenges in buying books, and problems related to weak eyesight, memory, and attention. It is important to investigate the situational motivation for reading among VT schoolchildren in their school library. The main tasks of educators and librarians are to evaluate schoolchildren’s reading practices and to uphold the prestige of reading in VT schools.